(untitled) (Global Journal of Management and Business Research, 2011)
This research propose the convenience of take into account the incidental liabilities in financial reporting about risks, in order to generate better financial information as a result of lack of criteria not only at international financial reporting standards, also in the United States, United Kingdom, Spain and Mexico. This research identifies and describes several risk ratings, considering the points of view of academics and in addition, considering the best practices of several well known multinational companies, focusing on the hospitality industry. Subsequently, the research concludes with a proposal in order to disclose incidental liabilities inspired by the format as international financial reporting standards provide, becoming this an unpublished material that contributes to standardization in the disclosure of risks across financial reporting standards.